Tributación y finanzas en trabajadores de la empresa centro comercial galerías Quispe Iquitos año 2023 - Flores Calampa, Jorge Junior (2025)
The present research work called “Taxation and finances in workers of the Quispe Shopping Center company in 2023”, was carried out using a descriptive study, and the design applied was non-experimental, it was developed with the general purpose of stipulating What is the degree of financial and tax knowledge in workers of the company called Quispe shopping center in the year 2023, for which there was a population sample of 75 workers, having used the survey technique and it was used as an instrument for collecting information was applied to the questionnaire, having obtained results that demonstrated that the degree of financial knowledge and tax knowledge in workers of the so-called Centro Comercial Quispe Iquitos company in 2023 is of a medium level.